Soil microbial community responses to fire - Fox, Sam (Kansas State University, 2022)
Fires, both wild and prescribed, have lasting impacts on the landscape and environment. Factors such as fire return interval, timing, and fire intensity and severity all play a role in the direct and indirect impacts fires have on the soil microbial communities (bacteria and fungi). Soil microbes play vital roles in soil stability, nutrient exchange, and many other ecosystem functions. Understanding how fires impact these communities is important for future land management decisions, especially in areas predicted to have more frequent and severe fires. In my dissertation, I first provide a synthetic review of what is currently known about the subject of fire impacts on fungi. This includes ecological frameworks, fungal fire traits, key fire-responsive fungal species, and community dynamics and trajectories. While this review is detailed and explores many facets of fungal responses to fire, I also address areas that still need to be explored, such as functional gene analysis following a fire, and having more controlled fire experiments. Second, I explored how fire frequency impacts the microbial communities residing in different soil horizons- A (topmost), E, and B (bottommost) as well as abiotic attributes that may be indirect drivers of community dynamics such as; Total N, Total C, SOM, inorganic N, P, and pH. For this project, we utilized an experimental infrastructure that had sixty years of continuously maintained, controlled fire regimes. This experiment included replicated experimental units that had been burned annually, every two years, and every four years, as well as a fire exclusion treatment that had not been burned in over sixty years. We observed that fire frequency impacts the microbial communities, but does so mainly in the topmost soil profile. The fire exclusion treatment differed from others when we compared the topmost soil horizons (where most microbial activity occurs). In almost all of our community and abiotic parameters, the fire interval manipulation treatments differed in the topmost A horizon, whereas the two deeper horizons E and B, had only a few parameters that differed between the fire interval treatments. Lastly, I investigate effects of low and high severity fires in a mid- to long-term experiment. This experiment manipulated fire severity and compared high and low severity fires to determine how the microbial communities change over a six-year time span. We also collected samples before the fire samples to enable comparisons to samples after fire to assess community recovery. My results suggested that the high-severity fires had a greater impact on the microbial communities compared to the low severity fires for both bacteria and fungi. Within the high severity fire sites, the communities remained distinct six years post-fire. In the low severity treatments, the communities started to resemble those before the fire, especially richness and diversity of the bacterial communities. This project allowed us to gain valuable understanding in microbial community trajectories following fire, and could aid in planning future restoration projects. Taken together, my dissertation research has allowed us to answer whether and how fire severity and frequency impact the soil microbial community. Indicator taxon analyses that I employed in both studies, identified taxa that seem to drive the community distinctions amongst the treatments, such as fungal taxa, Anthrocobia, Morchella, Pholiolata, and Pyronema which are described as pyrophilous taxa in my synthetic review. My dissertation research strongly indicates that microbial communities change with fire events and that these responses depend on fire interval and severity contexts. Whilst my studies provide considerable insight into the microbial responses to fire, the underlying reasons why they respond still remain complex and poorly understood. In all, fire changes soil chemistry, plant physiology and community composition, soil fauna, and many other system attributes that interact with microbial communities in soil. Exploring which of the many potential drivers are most important for microbial community fire responses and recovery remain a lingering area of research that needs to be explored.
Keywords: Fire; Bacteria; Fungi; Ecology; Community; Forest